2016
DOI: 10.3233/ch-16188
|View full text |Cite
|
Sign up to set email alerts
|

A novel two-dimensional quantitative shear wave elastography to make differential diagnosis of breast lesions: Comprehensive evaluation and influencing factors

Abstract: The lesion margin and vascularity could affect the measurement of SWS as well as the experience of examiner. However, VTIQ is still a reliable method that provides valuable information in the differential diagnosis of breast lesions, and may reduce unnecessary biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, the intra-operator and inter-operator consistency of quantitative shear wave speed measurements and QSWP were not assessed in our study. Previous studies showed that shear wave measurements were highly reproducible for assessing breast lesions and thus observer variability is not expected to have large influence on this study 23 , 24 . Second, only patients and lesions factors were evaluated for association with shear wave propagation quality, while equipment related factors (such as thermal noise, finite signal bandwidth, and the geometric spreading and absorbing of shear waves) were no studied 25 .…”
Section: Discussionmentioning
confidence: 97%
“…First, the intra-operator and inter-operator consistency of quantitative shear wave speed measurements and QSWP were not assessed in our study. Previous studies showed that shear wave measurements were highly reproducible for assessing breast lesions and thus observer variability is not expected to have large influence on this study 23 , 24 . Second, only patients and lesions factors were evaluated for association with shear wave propagation quality, while equipment related factors (such as thermal noise, finite signal bandwidth, and the geometric spreading and absorbing of shear waves) were no studied 25 .…”
Section: Discussionmentioning
confidence: 97%
“…In our experience, using the most recent reconstruction algorithm (Virtual Touch IQ–VTIQ) and very low precompression (to avoid artificial tissue stiffening), a cut-off value of 3.23 m/s shows a high area under the receiver operating characteristic (ROC) curve of 0.853 [ 22 ]. Other studies using VTIQ proposed in part similar, in part different cut-off values [ 23 , 24 ]. It is evident that more standardization is necessary, especially regarding the degree of precompression applied.…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
“…Recently, shear wave elastography (SWE), a specific ultrasound technique to quantify the stiffness of a lesion on imaging, showed promising results to reduce the number of unnecessary biopsies in some pilot trials [4][5][6][7][8][9][10][11] and one prospective multicenter trial [12]. SWE quantifies the stiffness of a lesion by evaluating the propagating speed of shear waves through the tissuethe output measurement is given either in meters per second (m/s) or kilopascals [13].…”
Section: Introductionmentioning
confidence: 99%